Common Femoral Artery Aneurysm: A Challenging Diagnostic and Treatment of a Rare Case - Ayu Asri Devi Adityawati; Novi Kurnianingsih; Budi Satrijo; Indra Prasetya (Heart Science Journal, 2021)
BACKGROUND: Aneurysm of peripheral artery is a rare vascular pathology, especially aneurysm in common femoral artery. Here, we presented a case report of right common femoral artery aneurysm caused by infectionCASE REPORT: a 76-year-old man referred to our hospital with pulsatile groin mass at his right thigh. He had no prior history of surgery or traumas, but he has been treated in private hospital due to septic condition, hypertension, and diabetes mellitus type II. Based on findings from physical examination and radiology examination, a diagnosis of common femoral artery aneurysm was made. The patient was referred to Cardiovascular and Thoracic Surgeon Department and scheduled for routine surgery, but on third day of admission patient became hemodynamically unstable and on re-examination it was found that the aneurysm had been ruptured. Emergency surgery was conducted on that day. During surgery patient was hemodynamically stable with PRC transfusion.DISCUSSION: Aneurysms can occur in almost any artery in the body. Femoral artery aneurysm was rare. Diagnostic procedure with various modalities were needed to establish a precise diagnosis for patient which come with swelling in his/her lower extremity. Doppler ultrasound was conducted in order to find a saccular mass with neck and a yin and yang phenomenon, which can narrow down the differential diagnosis to pseudoaneurysm or aneurysm. Subsequent CT angiography clearly confirmed the involvement of 3 layer arterial wall as a sign of an aneurysm. Femoral artery aneurysms (FAA) may be caused by weakening of the arterial wall due to atherosclerosis or mycotic aneurysm. Surgical repair of aneurysm is an option when symptomatic and that should also be considered when there is ongoing hemodynamic instability or limb ischemia.CONCLUSION: The common femoral artery aneurysm aren’t common. It is very rarely to be isolated aneurysm and usually don’t tend to be rupture. Whenever a femoral artery aneurysm is found, search and follow-up for other aneurysms should take place. Annual follow-up is recommended. Straightforward surgical management brings good results in this group of patient. Keywords: Femoral artery aneurysm, Common femoral artery aneurysm, Isolated aneurysm, Mycotic aneurysm